2015
DOI: 10.1212/wnl.0000000000002036
|View full text |Cite
|
Sign up to set email alerts
|

Arterial ischemic stroke in children with cardiac disease

Abstract: Infants with cyanotic CHD were most frequently affected by AIS during the periprocedural period. Prospective cohort studies are required to determine effective primary and secondary prevention strategies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(36 citation statements)
references
References 28 publications
1
31
0
Order By: Relevance
“…256 In a single-center Australian study, infants with cyanotic congenital heart defects undergoing palliative surgery were the highest-risk group to be affected by arterial ischemic stroke during the periprocedural period; stroke occurred in 22 per 2256 cardiac surgeries (1%). 257 …”
Section: Stroke (Cerebrovascular Disease)mentioning
confidence: 99%
“…256 In a single-center Australian study, infants with cyanotic congenital heart defects undergoing palliative surgery were the highest-risk group to be affected by arterial ischemic stroke during the periprocedural period; stroke occurred in 22 per 2256 cardiac surgeries (1%). 257 …”
Section: Stroke (Cerebrovascular Disease)mentioning
confidence: 99%
“…Children with cardiac disease are at known risk for AIS following cardiac procedures, especially children with cyanotic CHD. 8,21 Spontaneous AIS was reported three times more frequently than peri-procedural AIS. However, our study was not designed to directly compare peri-procedural versus spontaneous stroke risk; thus this finding should not be used to de-emphasize the risk of cardiac procedures.…”
Section: Discussionmentioning
confidence: 99%
“…Mackay et al found that postprocedural infection increases the odds of stroke fivefold in children with CHD after a cardiac procedure. 8 Acute infection at the time of sentinel stroke also has been reported to increase the risk of recurrent stroke in neonates and children with CHD. 14 Acute illness may further exacerbate the risk of thrombosis in children with cardiac disease by worsening acidosis (and potentially cardiac function) or decreasing oxygenation (e.g., those with pulmonary hypertension).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Cyanotic heart lesions incur the greatest risk of thromboembolic events, with an estimated 25% of pediatric arterial ischemic stroke attributable to congenital heart disease [3]. Small remnants of the right valve of the sinus venosus are common, being visible in over half of adult echocardiograms, but when prominent, such remnants have been linked to an increased risk of cryptogenic stroke [4].…”
Section: Introductionmentioning
confidence: 99%